2015
DOI: 10.1080/19420862.2015.1053683
|View full text |Cite
|
Sign up to set email alerts
|

Processing of complex N-glycans in IgG Fc-region is affected by core fucosylation

Abstract: (2015) Processing of complex N-glycans in IgG Fc-region is affected by core fucosylation, mAbs, 7:5, 863-870, DOI: 10.1080DOI: 10. /19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 Keywords: core fucosylation, sialylation, Nicotiana benthamiana, bisected glycans, glycan modelling, IgG, cetuximab Abbreviations: 3-FucT, Zea maize core a1,3-fucosyltransferase;3-FucT GnTIV, human a1,3-mannosyl-b1,4-N-acetyL-glucosaminyltransferase fused to the CTS region of the Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 50 publications
4
59
0
Order By: Relevance
“…Addition of 2FG also resulted in a slight decrease of fucosylation and a slight enhancement of high-mannose and hybrid-type glycans. Recently, it has been demonstrated that decorations of the IgG Fc N-glycan core affect the accessibility and consequently processing of Fc N-glycan antennae50. We speculate that the increased galactosylation observed with expression of the bisecting enzyme, GNTIII, as observed in our study, may be caused by the conformational change induced by bisection.…”
Section: Discussionsupporting
confidence: 74%
“…Addition of 2FG also resulted in a slight decrease of fucosylation and a slight enhancement of high-mannose and hybrid-type glycans. Recently, it has been demonstrated that decorations of the IgG Fc N-glycan core affect the accessibility and consequently processing of Fc N-glycan antennae50. We speculate that the increased galactosylation observed with expression of the bisecting enzyme, GNTIII, as observed in our study, may be caused by the conformational change induced by bisection.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to autopolysialylation of polySTs, Ig5FN1 required core fucose for polysialylation. It seems that this core glycan residue induces conformational modifications, thereby influencing the processing of glycan structures, an observation also noticed for the glycosylation modulation of the IgG-Fc N-glycan (19). Selective polysialylation determined by specific core residues has been reported for glycoproteins expressed in CHO cells (30).…”
Section: Discussionmentioning
confidence: 96%
“…1). Note that, for IgG sialylation, Arabidopsis thaliana α1,3-fucosyltransferase (FUT11) was transiently coexpressed because core α1,3-fucosylation enhances sialylation of the Fc glycans, which are naturally inefficiently sialylated (19). Transgenic ΔXTFT Sia plants stably express rat α2,6-sialyltransferase (ST6) and synthesize α2,6-linked Sia as previously shown using a transient expression approach (14).…”
Section: Stable Engineering Of An N-glycan Processing Pathway Toward Thementioning
confidence: 99%
“…Interestingly, the impact of core α1,3‐fucose on GlcNAc trimming shows that specific N ‐glycans on proteins like the Fc domain‐containing Sec‐Fc‐mRFP can be converted into HEXO3 substrates. The impact of core α1,3‐fucose on N ‐glycan modifications has been described recently for the N ‐glycan from the Fc domain of the monoclonal antibody cetuximab (Castilho et al ., ). In addition to the conserved Fc N ‐glycan, cetuximab has a second N ‐glycan in the variable domain of the heavy chain.…”
Section: Discussionmentioning
confidence: 97%
“…These two N ‐glycosylation sites on the heavy chain allow the comparison of N ‐glycan processing in a given cell in the presence or absence of an additional glycan modification. As a result of this study, it was shown that core α1,3‐fucosylation increases branching, bisecting GlcNAc formation and in particular sialylation of the Fc N ‐glycan presumably by alleviating structural constraints between the Fc N ‐glycan and the IgG1 CH2 domains (Castilho et al ., ).…”
Section: Discussionmentioning
confidence: 97%